Zoledronic Acid Versus Denosumab for Prevention of Spinal Cord Compression in Advanced Cancers With Spine Metastasis: A Meta-Analysis of Randomized Controlled Trials. Issue 6 (September 2020) - Al Farii, Humaid; Frazer, Abbey; Farahdel, Leila; Alfayez, Saud; Weber, Michael
Study Design: Meta-analysis of randomized controlled trials (RCTs). Objectives: The aim was to analyze the efficacy of zoledronic acid (ZA) versus denosumab in the prevention of spinal cord compression in patients with spine metastases from advanced cancers, by evaluating all available RCTs on this subject. Methods: A systematic search of electronic databases (PubMed and MEDLINE) was performed to identify all published RCTs comparing ZA with denosumab in prevention of spinal cord compressions in spine metastases. Risk of bias of the studies was assessed. The primary outcomes evaluated were spinal cord compression. Results: Three RCTs (5274 patients) were included. Denosumab was not significantly superior to ZA in reducing the likelihood of spinal cord compression, when all tumor types were combined (odds ratio [OR] 0.92, 95% confidence interval [CI; 0.66, 1.28], P = .66). Denosumab was not significantly favored over ZA in endodermal origin (breast and prostate; OR 0.72, 95% CI [0.43, 1.19], P = .20) and mesodermal origin tumors (solid tumors and multiple myeloma; OR 1.10, 95% CI [0.72, 1.69], P = .66). Conclusion: Denosumab does not significantly reduce the likelihood of spinal cord compressions in comparison to ZA in patients with spine metastases. When spinal cord compressions were grouped by tumor origin (endodermal or mesodermal), there remained no significant difference between denosumab and ZA. Further long-term studies are needed to determine the effectiveness of these treatment regimens.